A distance education experience on assessment of airway maneuvers during COVID-19 pandemic - Oktay, M Murat; Boğan, Mustafa; Sabak, Mustafa; Gümüşboğa, Hasan; Bilir, İbrahim and Demir, Mehmet Cihat and Narcı, Hüseyin (IMC Journal of Medical Science, 2021)
Background and objectives: The coronavirus disease 2019 (COVID-19) pandemic has necessitated the switch to distance education by abandoning face-to-face education worldwide. This study aimed to investigate whether it is possible for practical education and performance measurements through distance education. Methods: The application video and the application steps were sent to the participants through their smartphone by WhatsApp messenger. Grade 1 students in the Physiotherapy Section (Group A) and Grade 1 students in the Paramedic Section (Group B) voluntarily participated in the study. The participants were asked to apply simulation applications and record the simulation applications' video clips with their smartphones. Results: The mean age of the 123 participants was 20.11 ± 2.03 (18-33) years, and 56 (45.5%) were in Group A, and 67 (54.5%) were in Group B. While the participants in Group A were successful at a rate of 35.7% (n = 20) in the head tilt-chin lift maneuver, this rate was 65.7% (n = 44) for Group B (p = 0.001). For the jaw thrust maneuver, the success rate was 21.4% (n = 12) for Group A and 31.3% (n = 21) for Group B. Conclusion: In this study, the participants used family members as a live simulation model in our research. The participants who were given face-to-face education before were more successful on head tilt chin lift maneuver. Jaw thrust maneuver was more challenging to learn and practice by distance education. The academicians interested in medical education should keep in mind that the outcomes of the COVID-19 pandemic have permanent effects on education systems. Ibrahim Med. Coll. J. 2021; 15(1): 1-8